THE RIGHT TO SCHOOL EDUCATION AS A DIMENSION OF CITIZENSHIP IN MERCOSUR - Souza, Kellcia Rezende; Miceli Kerbauy, Maria Teresa [UNESP]; Silva, Rosalina Dantas da (Unesp-faculdade Ciencias & Letras, 2020)
School education is a human right and a fundamental dimension of citizenship, since it allows the enjoyment of other rights, such as: social, civil and political. It is, therefore, a basic component of human rights. Therefore, investigating the normative protection of educational law is a crucial task to understand, also, the citizenship status of a given country. In this sense, the study aims to analyze the constitutional order of the member countries (Argentina, Brazil, Paraguay, Uruguay and Venezuela) of the Southern Common Market (Mercosur) considering the guarantee of the right to education. For this, a bibliographic and documentary research was carried out with a qualitative approach. The documentary source was made up of the current constitutions of the countries. We note that the lack of existing legal and regulatory instruments in the constitutions may undermine progress in the effectiveness of educational law and, mainly, in achieving citizenship as an instrument of regional integration.
Keywords: Citizenship; Education rights; Educational internationalization; Mercosur